1973
DOI: 10.1104/pp.51.5.817
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Reductase Activity and Polyribosomal Content of Corn (Zea mays L.) Having Low Leaf Water Potentials

Abstract: Desiccation of 8-to 13-day-old seedlings, achieved by withholding nutrient solution from the vermiculite root medium, caused a reduction in nitrate reductase activity of the leaf tissue. Activity declined when leaf water potentials decreased below -2 bars and was 25% of the control at a leaf water potential of -13 bars. Experiments were conducted to determine whether the decrease in nitrate reductase activity was due to reduced levels of nitrate in the tissue, direct inactivation of the enzyme by low leaf wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
33
0
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 24 publications
3
33
0
1
Order By: Relevance
“…decreased slightly (Fig. 4 legend), presumably because the resistance to water flow through the cooled roots was higher, but at most this difference could account for only a 5% difference in NRA (14). The leaf nitrate content eventually decreased after 24 hr.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…decreased slightly (Fig. 4 legend), presumably because the resistance to water flow through the cooled roots was higher, but at most this difference could account for only a 5% difference in NRA (14). The leaf nitrate content eventually decreased after 24 hr.…”
mentioning
confidence: 99%
“…The effect of the different treatments was determined by measuring NRA after 5 hr under the treatment conditions. Previous work (4,14) showed that NRA in maize has a half-life of 4 to 4.5 hr. (8) found that NRA increased while nitrate was present in the exogenous medium, but fell as soon as the nitrate was removed, even though total cellular nitrate levels were relatively constant.…”
mentioning
confidence: 99%
“…Rapid changes in polyribosome levels are also known to occur in mosses (3,6). In other studies with higher plants, a number of workers have shown that polyribosome levels (4, 12,13) and protein synthesis (7,12,13) are reduced following stress; but in most cases, specific efforts were not made to determine how quickly these changes could occur. The study reported here was initiated to determine if polyribosome levels of several higher plants could be rapidly and consistently reduced by stress and to gain a better understanding of the possible relationships existing among polyribosome changes, cellular water status, and growth rates.…”
mentioning
confidence: 99%
“…Among the documented effects of water stress are: decreased tissue protein content (5,10), decreased incorporation of amino acids into protein (3,9), decreased nitrate reductase activity (19), increased ribonuclease activity (8,12), dissociation of polyribosomes (13,14), and altered mRNA transcription and translation (16). Changes in the pattern of protein synthesis during water stress have been observed in double-labeling experiments (6, 7) indicating that the effect is selective.…”
mentioning
confidence: 97%
“…Morilla et al (19) have shown that nitrate reductase activity in maize is severely inhibited by mild water stress; however, no data are available for nonnodulated hydroponically grown soybeans. The possibility that ovules might be able to reduce nitrate is precluded by the work of Thompson et al (23).…”
mentioning
confidence: 99%